Spectral impact on PV performance in mid-latitude sunny inland sites: Experimental vs. modelled results. (15th December 2017) - Nofuentes, Gustavo; de la Casa, Juan; Solís-Alemán, Ernesto M.; Fernández, Eduardo F.
Abstract: The influence of spectral irradiance on the performance of different PV materials—amorphous silicon, CdTe, CIS, and monocrystalline silicon—is studied in two cities assumed representative of mid-latitude inland sunny sites not affected by extreme atmospheric characteristics. Experimental and modelled spectral mismatch factors at different timescales—instantaneous, monthly, and annual—were derived from a) outdoor spectra recorded over a 24-month experimental campaign conducted in Madrid and Jaén (Spain) and b) synthetic spectra computed using SMARTS and input atmospheric data from AERONET. The experimental annual spectral gains presented here lie within ±1% for all PV materials under scrutiny in both sites, in close agreement with modelled results. In practical terms, this may lead to simpler PV modelling approaches by neglecting spectral effects on an annual basis in sites with spectral characteristics similar to Madrid's and Jaén's. Modelled spectral impacts on PV performance previously reported for these two cities are qualitatively well aligned with our findings. Interestingly, absolute differences between the results regarding the annual spectral influence on monocrystalline silicon and CdTe in both sites obtained by means of a model based on satellite-based spectrally resolved irradiance data and the experimental results for these materials presented here stay below 0.3%. Highlights: Spectral impact on PV in two cities representative of mid-latitude inland sunny sites. Two-year spectral irradiance datasets recorded at two Spanish sites. Modelling spectra using SMARTS in conjunction with AERONET. Experimental annual spectral gains lying within ±1%, aligned with modelled results. Empirical validation in modelled spectral gains reported for the two studied sites.